Evaluating the Environmental Impact of Ethanol Fuel: Particle Number Emissions in Flex-Fuel Vehicles (Global Journal of Human-Social Science, 2023)
In Europe, the EURO 6 Light Duty emission standards, a consequence of Diesel vehicles, introduced limits for particle number (PN) of Gasoline Direct Injection (GDI) engines. Given the extremely small particles' concern about health effects, the same limits were set (6.0 x 1011 #/km) for diesel and GDI cars. In Brazil, the current phase for light vehicles of PROCONVE L6 enforced particulate matter (PM) mass emission standards for Diesel vehicles only, applying the limits of 25 mg/km for passenger cars and 30 mg/km for commercial vehicles. Similar to the European concern, even not considering the particle number (PN) emissions, future Brazilian phase L7, which is under study, considers a significant reduction in the limit of the particulate matter (PM) mass emission from current limits down to 6 mg/km for both Diesel and DI engines, for passenger and commercial vehicles. Aiming to contribute to hydrated ethanol fuel sustainability discussion compared to gasoline and for generating reference data regarding particle number (PN) emissions, which can be used for future emissions regulations of Flex-Fuel vehicles in the Brazilian market, this article explores particle number (PN) measurements of Flex-Fuel Vehicles equipped with direct injection (DI) and port fuel injection (PFI) engines, fueled with ethanol (E100) and gasohol (E22).
Keywords: ethanol; sustainability; particle number; particle matter